2020 International Conference on UK-China Emerging Technologies (UCET) 2020
DOI: 10.1109/ucet51115.2020.9205355
|View full text |Cite
|
Sign up to set email alerts
|

Fully-Transparent Transmission Surface for Outdoor-Indoor mmWave Coverage Enhancement

Abstract: This paper presents a fully-transparent and novel frequency selective surface (FSS) that can be deployed instead of conventional glass to reduce the penetration loss encountered by millimeter wave (mmWave) frequencies in typical outdoorindoor (O2I) communication scenarios. The presented design uses a 0.035 mm thick layer of indium tin oxide (ITO), which is a transparent conducting oxide (TCO) deposited on the surface of the glass, thereby ensuring the transparency of the structure. The paper also presents a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Various FSSs have been developed to fulfill diversified design requirements. Different shapes have been studied, from simple cross dipoles, loops, hexagonal and circular disks to advanced Jerusalem crosses and slotted patches and to their combinations [2]. However, these unit cells are based on try and error approach and requires timely process.…”
Section: A Ga-based Unit Cell Designmentioning
confidence: 99%
“…Various FSSs have been developed to fulfill diversified design requirements. Different shapes have been studied, from simple cross dipoles, loops, hexagonal and circular disks to advanced Jerusalem crosses and slotted patches and to their combinations [2]. However, these unit cells are based on try and error approach and requires timely process.…”
Section: A Ga-based Unit Cell Designmentioning
confidence: 99%
“…The authors in [14] designed new IOS elements and arranged them in a hexagonal lattice structure. Simulation results showed that substituting a part of a wall with an IOS can improve the coverage probability for the outdoor-to-indoor mmWave communication system.…”
Section: Introductionmentioning
confidence: 99%
“…It is being foreseen that smart technologies such as smart antenna systems, transmission surfaces, and reconfigurable intelligent surfaces (RIS) with dynamic beam steering capabilities would be vital elements of such future networks. 1 , 2 , 3 Smart antenna systems typically rely on either an adaptive array or beam-switching systems with the former offering better performance than the latter but at the expense of higher complexity and implementation cost. This is majorly due to the use of phase shifters in such adaptive-array antennas which are costly and can suffer from an inherent loss at microwave frequencies.…”
Section: Introductionmentioning
confidence: 99%